Biochar-based black ink
The use of biochar pigments and 100% BRC rosin adducts in ink formulations addresses the challenge of achieving high bio-renewable carbon content, ensuring microwave safety and performance in printing applications.
Patent Information
- Application Number
- JP2024500556
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-07-13
- Filing Date
- 2022-07-11
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-07-11
AI Technical Summary
The printing ink industry faces challenges in achieving high bio-renewable carbon (BRC) content while maintaining the necessary physical properties for printing, particularly in microwave safety and compatibility with sustainable carbon sources, as existing technologies struggle to formulate inks with 100% BRC without compromising performance.
The development of black inks and coatings using pyrolyzed cellulose (biochar) pigments and 100% BRC rosin adducts, combined with specific formulations to ensure compatibility and performance, including the use of rosin-citrate ester resin to manage hydrogen bonding and viscosity, achieving a 100% BRC composition.
The solution provides black inks and coatings with 100% BRC content that are microwave safe and meet the requirements of rotogravure and flexographic printing, demonstrating robust performance in various packaging applications, including microwave safety and resistance to mechanical stress.
Smart Images

Figure 0007610073000001 
Figure 0007610073000002 
Figure 0007610073000003
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Application No. 63 / 221,153, filed July 13, 2021, which is hereby incorporated in its entirety.
[0002] The present invention relates to black inks and coatings containing high bio-renewable carbon. The inks and coatings contain water, pyrolyzed cellulose (e.g., Biochar) pigments, and rosin adducts. The inks and coatings of the present invention are microwave safe. [Background technology]
[0003] For several years, the printing ink industry has been trying to build products using the maximum amount of renewable and responsibly sourced carbon. Raw material limits include the percentage of sustainably sourced carbon, as well as the chemicals required to provide acceptable physical performance.
[0004] In printing inks, there are two general forms of carbonaceous material. The first form of carbonaceous material represents high BRC (bio-renewable content) materials, i.e. those with carbon originating from recent growing sources (naturally occurring materials). The second type are raw materials originating from ancient carbon (e.g. petroleum, coal) that are considered low or zero BRC. The trend in responsible ink formulations is to replace low BRC materials with higher BRC materials in order to reduce the environmental and climate impact of the final decomposition product, carbon dioxide. Within the ink industry, one method for BRC measurement as a percentage of the total carbon in a material is the measurement of the carbon-14 isotope ( 14 C) vs. Carbon-12 isotope ( 12 The goal of carbon-14 testing is to measure the ratio of beta radiation emitted per microgram of carbon content and compare it to a known standard. Carbon-14 testing, commonly referred to as "carbon dating", determines the age of a sample by counting the amount of beta radiation emitted per microgram of carbon content.14 Given the 5730 year half-life of C, in any sample known to contain raw material less than 300 years since its last inhabitant, the relative proportion of sustainable (BRC) carbon and even the proportion of ancient carbon can be determined by counting beta emissions. The BRC method has several challenges, including for the period 1950 to 2015. Between 1950 and 1963, above-ground nuclear explosions caused a large amount of carbon dioxide in the Earth's atmosphere. 14 The C content increased by 190% as CO2. 14 The amount of C peaked in 1963, and since then, Earth's plants have been over-reacting. 14 C, and in 2015 14 C back to pre-1950 levels. These years are also part of the historical reference for BRC comparisons. If the age (since living) of the test sample is known, the BRC can be accurately normalized for material living from 1950 to 2015.
[0005] WO 2021 / 062312 discloses vegetable carbon pigments, which may be provided as liquid dispersions. The vegetable carbon pigments are produced by pyrolyzing carbohydrates (i.e., plant material). The pigment dispersion may include microfibrillated cellulose, which is included in the milling fluid. Microfibrillated cellulose is a particulate form of cellulose, a polysaccharide that can act as an anticoagulant by intercalating between pigment particles, but is insoluble in water.
[0006] WO 2021 / 231829 describes inks and coatings with high BRC that contain rosin adducts. There is no disclosure of biochar used as a pigment. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2021 / 062312 [Patent Document 2] International Publication No. 2021 / 231829 Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention relates to black inks and coatings containing high bio-renewable carbon. The inks and coatings contain water, pyrolyzed cellulose (e.g., Biochar) pigments, and rosin adducts. The inks and coatings of the present invention are microwave safe. [Means for solving the problem]
[0009] The present invention provides black ink and coating compositions containing 70% to 100% BRC relative to the total carbon in the composition. This is the first time it has been shown that pyrolyzed carbohydrates (e.g., biochar) can be used in a finished ink or coating, which has the necessary physical properties to meet the requirements of the printing industry.
[0010] The black ink and coating compositions of the present invention include water, a biochar pigment, and a rosin adduct, the rosin adduct having 100% bio-renewable carbon (BRC) content.
[0011] In a particular aspect, the present invention provides a water-based liquid black ink composition comprising: (a) 30% by weight to 50% by weight of a mixed vehicle based on the total weight of the ink composition, i. 10% to 30% by weight of water based on the total weight of the mixed vehicle; ii. an L-lactic acid mixture comprising 5% by weight to 15% by weight of the L-lactic acid mixture based on the total weight of the mixed vehicle, and comprising 88% by weight of L-lactic acid and 22% by weight of water based on the total weight of the L-lactic acid mixture; iii. 10% to 30% by weight of a rosin adduct, based on the total weight of the mixed vehicle; iv. 10% to 30% by weight of 14.5 Baume ammonia based on the total weight of the mixed vehicle; v. 1 wt.% to 10 wt.% of a wax suspension, based on the total weight of the mixing vehicle, the wax suspension comprising 25 wt.% wax and 75 wt.% water, based on the total weight of the wax suspension; vi. 1% to 5% by weight of a micronized wax, based on the total weight of the mixed vehicle; vii. 0.05% by weight to 1% by weight of a silicone compound based on the total weight of the mixed vehicle; viii. A mixed vehicle comprising 0.5% by weight to 3% by weight of a zinc chelating agent based on the total weight of the mixed vehicle; (b) 50% by weight to 70% by weight of a black dispersion liquid based on the total weight of the ink composition, i. 10 wt.% to 40 wt.% biochar based on the total weight of the black dispersion; ii. 1 wt.% to 5 wt.% of a surfactant, based on the total weight of the black dispersion; iii. 5% to 20% by weight of the mixed vehicle of part (a) based on the total weight of the black dispersion; iv. A black dispersion comprising 10% by weight to 50% by weight of water based on the total weight of the black dispersion; A water-based liquid black ink composition is provided, wherein 75% to 100% of the carbon content in the ink composition is bio-renewable carbon (BRC).
[0012] In some embodiments, the rosin adduct is a 100% BRC rosin ester resin, preferably a rosin-citrate ester resin.
[0013] In some embodiments, the ink and coating compositions of the present invention comprise 100% BRC.
[0014] These and other objects, advantages and features of the present invention will become apparent to those skilled in the art upon reading the details of the compositions and methods that are more fully described below. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Detailed Description of the Invention The present invention is the first disclosure of a 100% BRC carbon-containing pigment material (e.g., biochar) that, when used in combination with a 100% BRC ink resin and a 100% BRC ink additive, is used to produce a fully functional printing ink. The solution provided by the present invention is a combination of biochar and a 100% BRC rosin adduct that exhibits a comprehensive set of ink performance properties, as described below.
[0016] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of any subject matter claimed.
[0017] Headings are for organizational purposes only and are not intended to limit the invention in any way.
[0018] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention belongs. All patents, patent applications, published applications, and publications, websites, and other published materials mentioned throughout this disclosure are incorporated by reference in their entirety for any purpose unless otherwise noted. Although any methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present invention, preferred methods are described.
[0019] definition In this application, the use of the singular includes the plural unless specifically stated otherwise. As used herein, the singular forms "a," "an," and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.
[0020] In this application, the use of "or" means "and / or" unless otherwise stated. Also, if clear from the context in which it is used, "and" may be interpreted as "or", such as a list of alternatives, none of which may all be true or exist at once.
[0021] As used herein, the terms "comprises" and / or "comprising" specify the presence of stated features, integers, steps, operations, elements, and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or groups thereof. Furthermore, to the extent the terms "includes," "having," "has," "with," "composed," "comprised," or variations thereof are used in either the detailed description or the claims, such terms are intended to be inclusive in a similar manner as the term "comprising."
[0022] When the terms "consist of," "consists of," or "consisting of" are used in the body of a claim, the claim term beginning with "consist of," "consists of," and / or "consisting of" is limited to the elements recited immediately following "consist of," "consists of," or "consisting of," and is closed to the unrecited elements associated with that particular claim term. The term "combinations thereof," when included in the list of recited elements following "consist of," "consists of," or "consisting of," means a combination of two or more of the recited elements.
[0023] As used herein, ranges and amounts can be expressed as "about" a particular value or range. "About" is intended to include the exact amount. Thus, "about 5 percent" means "about 5 percent" and also means "5 percent." "About" means within typical experimental error for the intended use or purpose.
[0024] When a numerical range is recited, it is understood that it includes the endpoints, all values within that range, and all narrower ranges within that range, whether or not they are specifically recited.
[0025] Throughout this disclosure, all parts and percentages are by weight (weight % or mass % based on total weight) and all temperatures are in °C unless otherwise indicated.
[0026] As used herein, "natural materials" are plant-based, mineral-based, animal-based materials derived from microorganisms, their reaction products, and combinations thereof, and water. Natural materials can be used as they occur in nature, or can be subjected to processing that does not significantly change the original physical, chemical, or biological state of the components. Examples of acceptable processing include dehydration, extraction, extrusion, centrifugation, filtration, distillation, grinding, sieving, pressing, freezing, drying, milling, and the like. Natural materials include, but are not limited to, water, natural resins, natural defoamers, natural waxes, natural colorants, biosolvents, natural minerals, and the like.
[0027] As used herein, "BRC" refers to biorenewable carbon, which may be further defined as non-ancient carbon (i.e., non-fossil carbon) that is part of the Earth's natural environment. Non-ancient carbon (less than 40,000 years since final atmospheric carbon incorporation) is radiocarbon ( 14C), whereas ancient (fossil) carbon does not contain radioactive carbon. BRC refers to a naturally occurring renewable resource that can be replenished either through natural renewal or other recurring processes within a limited time (such as a human lifetime) to replace that which is depleted through use and consumption.
[0028] As used herein, "plant-based" refers to a material that contains 50% or more of its component mass from a plant-based source.
[0029] As used herein, "naturally derived" refers to materials that have 50% or more natural or bio-based origin by molecular weight based on renewable carbon content.
[0030] As used herein, a "natural mineral" refers to an inorganic material that occurs naturally on Earth, having a unique chemical formula and a consistent set of physical properties (e.g., crystal structure, hardness, color, etc.), and a "derived mineral" is a material that is obtained through chemical processing of an inorganic material that occurs naturally on Earth, having the same chemical composition as a natural mineral component (e.g., calcium carbonate, silica, hydrated silica, sodium fluoride, titanium dioxide).
[0031] As used herein, "bio-based" refers to carbon-containing materials of renewable origin from agricultural, plant, animal, fungal, microbial, marine, or forestry materials.
[0032] As used herein, "pyrolyzed carbohydrates," "pyrolyzed cellulose," and "biochar" refer to carbonaceous materials obtained by the partial combustion or pyrolysis of vegetable and fruit waste, bones, horns, ivory, and similar materials. Pyrolysis involves placing the material in a chamber and heating it in the presence of little or no oxygen.
[0033] As used herein, "renewable" refers to materials that are part of the earth's natural environment. Renewable resources occur naturally and can be replenished, either through natural renewal or other recurring processes, for a limited time (such as within a human lifetime) to replace those portions that are depleted through use and consumption.
[0034] As used herein, "mixed vehicle," "varnish," and "ground varnish" refer to compositions of the present invention that do not contain pigment. The mixed vehicle, varnish, or ground varnish may be mixed with pigment and used as a pigmented ink or coating, or may be used as is (i.e., without pigment) as a clear coating.
[0035] As used herein, "sustainable" refers to the quality of not being harmful to the environment or depleting natural resources, thereby supporting long-term ecological balance.
[0036] As used herein, "substrate" refers to any surface or object to which an ink or coating can be applied. Substrates include, but are not limited to, cellulosic substrates, paper, paperboard, fabrics (e.g., cotton), leather, textiles, felt, concrete, masonry, stone, plastics, plastic or polymeric films, spunbond nonwovens (e.g., made of polypropylene, polyester, etc.), glass, ceramic, metal, wood, composites, combinations thereof, and the like. The substrate may have one or more layers of metal or metal oxide, or other inorganic materials. Nonwoven substrates are particularly preferred.
[0037] As used herein, the term "article" or "articles" refers to a substrate or an article of manufacture. Examples of articles include, but are not limited to, substrates such as cellulosic substrates, paper, paperboard, plastic, plastic or polymeric films, glass, ceramic, metal, composites, and articles of manufacture such as publications (e.g., booklets), labels, and packaging materials (e.g., cardboard sheets or corrugated board), containers (e.g., bottles, cans), polyolefins (e.g., polyethylene or polypropylene), polyesters (e.g., polyethylene terephthalate), metallized foils (e.g., laminated aluminum foil), metallized polyesters, metal containers, and the like.
[0038] As used herein, "inks and coatings," "inks," and "coatings" are used interchangeably and refer to compositions of the present invention or, where specified, compositions found in the prior art (comparison). Inks and coatings typically contain a resin, a solvent, and optionally, in some cases, a colorant. Coatings are often considered to be colorless or transparent, while inks typically include a colorant.
[0039] As used herein, the "side" of a printed or coated substrate refers to the side to which the ink or coating is applied.
[0040] As used herein, the "back side" of a printed or coated substrate refers to the side that does not have an ink or coating applied to it.
[0041] As used herein, an "unsaturated compound" is a carbon-containing material that contains one or more C=C bonds (carbon-carbon double bonds).
[0042] water-based composition The present invention provides a water-based black liquid ink with the necessary physical properties to perform within rotogravure and flexographic printing requirements using 100% bio-renewable carbon components. The unique structure and interaction of the materials are key features that lead to a fully functional ink product. WO 2021 / 162312 suggests that biochar can be used to pigment the finished ink, but only pigment dispersions are described, not finished inks. Furthermore, WO 2021 / 162312 does not disclose the use of rosin resin adducts in combination with biochar. The microfibrillated cellulose used in WO 2021 / 162312 is a particulate form of cellulose, a polysaccharide that can function as an anticoagulant by intercalating between pigment particles. It is not water-soluble and does not have the function of a dispersant. The rosin resin used in the present invention is a terpene chemical derived from natural rosin, which is modified to function as a dispersant by adsorbing to pigment particles and providing steric and ionic interactions to prevent the particles from agglomerating. Those skilled in the art will recognize that the microfibrillated cellulose and the rosin resin adduct of the present invention are not equivalent and cannot be used interchangeably.
[0043] Printing inks (and coatings) are composites of multiple raw materials, each of which contributes a part to the overall performance, and all of which must be compatible with each other to ensure chemical stability over time. Those skilled in the art will recognize that water-based printing inks typically contain about 30-40% carbon-containing compounds, 60% or more water, and about 1% ammonia. Carbon contribution takes into account both the amount of carbon-containing compounds in the formulation, and the amount of elemental carbon in each individual compound. Representative carbon-containing compounds are summarized in Table A with respect to their relative elemental carbon contribution.
[0044] [Table 1]
[0045] The ink and coating compositions of the present invention preferably have a BRC contribution of 100% for all elemental carbon-containing compounds. That is, it is preferred that the elemental carbon in any component of the present invention is not less than 100% BRC. Pigment content is a major challenge for 100% BRC inks due to the lack of sustainable carbon (dye) intermediates, commonly sourced from China, used to manufacture organic pigments. Considering that organic colorants make up nearly half of the carbon content of a typical liquid ink, this fact appears to be severely limiting the construction of 100% BRC finished inks. Many carbon black pigments and pigment dispersions commercially available products that contain sustainable carbon content do not achieve 100% BRC. One example of a carbon black that has a partially sustainable content but does not achieve 100% BRC is Orion's Printex Nature Black. This lamp process pigment uses incomplete combustion of 100% BRC soybean bran wax to produce a high BRC black pigment, but the BRC is listed in the literature as 85%. Upon further inspection, natural gas (of ancient origin) is used to power the combustion process, resulting in unsustainable carbon in the final pigment product.
[0046] Microwave sensitivity is known as an advantage for heating foods, but this is the responsibility of the printed ink. Printed inks (especially many carbon blacks) often exhibit heat, smoke, sparks, and flame production when exposed to microwave energy. Few ancient sources (e.g., petroleum-based) of high-purity carbon pigments are microwave-safe because the carbon content is so high. Carbon pigments with oxygen content above 4% tend to be microwave-safe due to the insensitive properties of oxygen. Biochar pigments derived from modern living organisms typically contain oxygen content above 4% (from residual lignin and cellulose structures) and are typically microwave-safe.
[0047] Compostability is a characteristic of chemical decomposition via heat, light, chemical reactions, and microbial metabolic activity. Without being bound by theory, the consensus is that ink components that are closer to living, natural structures tend to be more readily metabolized by microorganisms than highly chemically modified compounds that no longer resemble natural food structures.
[0048] The finished ink has special formulation considerations with biochar and ancient source carbon black pigments. These considerations include rheological and viscosity stability, application density (pigment delivery at desired viscosity), solids at desired viscosity, and flexo and rotogravure delivery to the substrate. All of these performance considerations are based on the cohesive and adhesive interactions between the components in the ink. The main difference between biochar carbon and ancient source carbon is the oxygen content (tendency to form hydrogen bonding interactions) and structural resistance to mechanical disintegration.
[0049] Within the finished ink, there are hydrogen bonding interactions between the resin and the pigment due to attractive forces. Those skilled in the art will explain the functional amount of hydrogen bonding chemistry required for both the resin and the pigment. Too little hydrogen bonding will not produce the adhesion and cohesion required for wet delivery from the anilox to the plate to the substrate. On the other hand, if both the resin and pigment contain excess hydrogen bonding structures with geometries to delocalize the attractive forces, the result is an increase in viscosity for a given amount of solids present in the composition. Higher viscosities will require the addition of more water to achieve print viscosity, and a loss of pigment percentage (i.e., lower applied color strength). In the specific example of biochar black pigment (as opposed to ancient source carbon black), greater hydrogen bonding character exists as residual oxygen structures from the cellulose. This is attenuated by resin selection (e.g., rosin citrate) with one pole of the structure with little / no hydrogen bonding structures. This geometry localizes the attractive forces of the pigment (i.e., localizes to one pole with more hydrogen bonds).
[0050] Formulating for optimal ink rheology attempts to minimize wet suction forces without eliminating those same suction forces in the dry printing ink. Biochar pigments need to be combined with agents that reduce hydrogen bonding, producing greater flow, greater application solids, and less viscosity. One such agent to isolate the excess oxygen content of biochar and reduce suction forces is the 100% BRC rosin adduct used in this invention.
[0051] Examples of rosin adduct materials include, but are not limited to, Lawter's Filtrez rosin fumarate, Lawter's Reactol rosin-based polyesters, and Polimeros Sinteticos' Amberyl rosin maleate.
[0052] In a preferred embodiment, the rosin adduct used in the present invention is an anionic modified rosin resin ester. The preparation of the rosin adduct is described in WO 2021 / 231829. Colophony consisting of rosin monomers and dimer acids is first reacted with a material of the general structure called alpha hydroxy carboxylic acid. Examples of alpha hydroxy carboxylic acids include, but are not limited to, malic acid, fumaric acid, lactic acid, tartaric acid, ascorbic acid, citric acid, glycolic acid, hydroxycaproic acid, hydroxycaprylic acid, mandelic acid, phytic acid, and combinations thereof. This first reaction produces a rosin ester. A second reaction with any number of polyols can result in a high molecular weight modified rosin ester. Rosin may also be polymerized with any number of unsaturated compounds using free radical propagation methods. A particularly preferred material is 100% BRC rosin-citric acid ester resin. The rosin adduct material is preferably modified with lactic acid.
[0053] These 420-920 molecular weight modified rosins exhibit a pole with zero hydrogen bonding sites and another pole with hydrogen bonding sites that cannot interact with more than one biochar particle, eliminating the delocalization of attraction forces and the increase in viscosity. In other words, long strings of attraction forces require more energy to move than short localized ones. Some examples of rosin-citrate ester resin structures are shown below (from WO 2021 / 231829):
[0054] [Table 2]
[0055] Biochar pigments are commercially available and come in a range of particle size options. Biochar pigments differ from ancient carbon black pigments in their high resilience to mechanical disintegration. Biochar tends to absorb mechanical energy without grinding to a smaller average particle size, resulting in bending of the structure rather than avoiding it. The use of black pigments in printing inks requires particle size reduction to approximately 1 μm or less to optimize light absorption efficiency. Established particle reduction techniques exist and are known in the ink industry as milling. One common established process for reducing (fracture resistant) particles is a premix step with chemicals that chemically penetrate microcracks. Similar to the expansion of cracks in glass where water penetrates, freezes, and expands, surfactant chemistry is commonly utilized in the ink industry to chemically penetrate difficult to grind pigments, enhancing the mechanical reduction process. It is noted that biochar suppliers have additional mechanical techniques and equipment for particle size reduction.
[0056] A key attribute of this invention is the achievement of near 30% non-pigment solids with a printing viscosity of near 28 seconds on a #2 EZ Zhan cup viscometer. Successful delivery of the ink to the substrate has a complex relationship to both solids and viscosity. Resin solids are the primary factor providing the physical performance of the printing ink. Pigment solids (biochar) are the primary factor providing the color strength. It is paramount that the resin and pigment combination do not interact to the point of high viscosity and low solids. The formulation of this invention exhibits low viscosity, high solids compatibility of rosin-citrate ester resin with biochar.
[0057] Robust mechanical abrasion resistance in printing inks is a combination of surface hardness (determined by the pencil hardness test of the present invention) and flexibility. When the glass transition temperature (Tg) of the ink or coating is below 25°C, optimal flexibility is achieved so that a film forms at approximately room temperature. Most packaging has typical packaging applications near room temperature, i.e., about 22°C to about 30°C. If the Tg is below room temperature, the polymers and additives exhibit elasticity and toughness at 25°C. Resins with a Tg below the packaging use temperature are film formers. If the Tg is higher, e.g., about 50°C, and the package is mechanically stressed at 30°C, the ink may crack / shatter / powder. Conversely, if the Tg is much below the package use temperature, the ink will smear and transition more easily than if the Tg is closer to the use temperature. This situation can be described as "tacky". Surface hardness is always a mechanical advantage at higher levels where film formation is present. Historically, flexible packings with pencil hardness and film formation above 2H would exhibit robust mechanical resistance.
[0058] The block resistance of a printed substrate is the prevention of ink being transferred to the unprinted side of the substrate when the substrate is rolled. A practitioner in the art uses a laboratory block test apparatus that generates 50 psi, 120° F. (about 49° C.) and 66% relative humidity for a duration of more than 72 hours to simulate the transportation of prints in a hot truck. The printed sample is rolled up to create a face-to-face configuration before being loaded into the block test apparatus.
[0059] Heat resistance is a requirement for many packaging applications due to the use of hot forming equipment. A common replication of kinetic heat resistance is the use of a heated sled (400°F, or approximately 204°C) in conjunction with a Sutherland Rub Tester. A second static heat resistance test utilizes a Sentinel Heat Sealer, placing the printed sample between aluminum foil. The foil is exposed to 400°F and 80 psi to evaluate the transfer of the ink to the foil. The benefit of achieving and confirming heat resistance is that it prevents transfer and lamination of the printing ink on the hot forming equipment.
[0060] Unique packaging applications have additional (specific) performance requirements. For example, the fast food industry places great importance on sustainability and improved BRC in packaging. Fast food uses sandwich wraps, to-go bags, folding cartons, polyethylene (PE) cups, and pre-printed corrugated packaging. In these applications, the ink must withstand the solubility of soft drinks (simulated by wet napkin friction), contact with condiments without displacing the ink, and no ink transfer within stacks of nested containers. The ultimate proof of a functional 100% BRC black ink is to achieve all the required properties simultaneously.
[0061] Several finishing ink examples shown in this application work well for many common application requirements using the proprietary 100% BRC Varnish as the grind / mix vehicle or as a coating where applicable / necessary.
[0062] In one embodiment, the present invention provides a water-based varnish composition that can be used as a coating (i.e., referred to as a coating or varnish as such), a pigment grind vehicle, or a mixing vehicle for an ink composition (mentioned in the examples). Use of any of these terms refers to a water-based varnish. The varnish / grind vehicle / mixing vehicle comprises a rosin adduct and water. In some embodiments, the varnish / grind vehicle / mixing vehicle further comprises one or more of L-lactic acid, ammonia, a wax, a silicone compound, or a chelating agent.
[0063] The varnish / grind vehicle / mixing vehicle typically contains about 10% to about 30% by weight of water based on the total weight of the varnish. For example, the varnish / grind vehicle / mixing vehicle may contain about 10% to about 25% by weight of water, or about 10% to about 20% by weight, or about 10% to about 15% by weight, or about 15% to about 30% by weight, or about 15% to about 25% by weight, or about 15% to about 20% by weight, or about 20% to about 30% by weight, or about 20% to about 25% by weight, or about 25% to about 30% by weight, based on the total weight of the varnish / grind vehicle / mixing vehicle.
[0064] The varnish / grind vehicle / mixing vehicle typically contains about 10% to about 30% by weight of the rosin adduct based on the total weight of the varnish. For example, the varnish / grind vehicle / mixing vehicle may contain about 10% to about 25% by weight of the rosin adduct, or about 10% to about 20% by weight, or about 10% to about 15% by weight, or about 15% to about 30% by weight, or about 15% to about 25% by weight, or about 15% to about 20% by weight, or about 20% to about 30% by weight, or about 20% to about 25% by weight, or about 25% to about 30% by weight, based on the total weight of the varnish / grind vehicle / mixing vehicle.
[0065] When present, the varnish / grinding vehicle / mixing vehicle typically comprises about 5% to 15% by weight of the L-lactic acid composition. For example, the varnish / grinding vehicle / mixing vehicle may comprise about 5% to about 10% by weight of the L-lactic acid composition, or about 10% to about 15% by weight, based on the total weight of the varnish / grinding vehicle / mixing vehicle. The L-lactic acid composition is typically provided as a dispersion / solution in water, comprising about 88% by weight of L-lactic acid and about 22% by weight of water.
[0066] When present, the varnish / grind vehicle / mixing vehicle typically comprises from about 10% to about 30% by weight of the ammonia composition, based on the total weight of the varnish / grind vehicle / mixing vehicle. For example, the varnish / grind vehicle / mixing vehicle may comprise from about 10% to about 25% by weight of the ammonia composition, or from about 10% to about 20% by weight, or from about 10% to about 15% by weight, or from about 15% to about 30% by weight, or from about 15% to about 25% by weight, or from about 15% to about 20% by weight, or from about 20% to about 30% by weight, or from about 20% to about 25% by weight, or from about 25% to about 30% by weight, based on the total weight of the varnish / grind vehicle / mixing vehicle. The ammonia composition is typically provided as 14.5 Baume ammonia.
[0067] The wax may be included in the varnish / grind vehicle / mixing vehicle as a wax suspension or as micronized wax. Preferably, the wax is a natural wax containing 75% to 100% BRC. If present, the wax suspension is typically present in an amount of about 1% to 10% by weight of the wax suspension, based on the total weight of the varnish / grind vehicle / mixing vehicle. For example, the varnish / grind vehicle / mixing vehicle may contain about 1% to about 5% by weight of the wax suspension, or about 5% to about 10% by weight, based on the total weight of the varnish / grind vehicle / mixing vehicle. The wax suspension is typically provided as a suspension containing about 25% by weight of wax and about 75% by weight of water. If present, the varnish / grind vehicle / mixing vehicle typically contains about 1% to about 5% by weight of the micronized wax, based on the total weight of the varnish / grind vehicle / mixing vehicle. Suitable wax suspensions include, but are not limited to, amide waxes (e.g., ethylene bisstearamide (EBS) wax), erucamide wax, polypropylene wax, paraffin wax, polyethylene wax, polytetrafluoroethylene wax, carnauba wax, soy wax, and combinations thereof.
[0068] When present, the varnish / grind vehicle / mixing vehicle typically comprises from about 0.05% to about 1% by weight of a silicone compound, based on the total weight of the varnish / grind vehicle / mixing vehicle. When present, the varnish / grind vehicle / mixing vehicle typically comprises from about 0.5% to about 3% by weight of a chelating agent, based on the total weight of the varnish / grind vehicle / mixing vehicle. In certain embodiments, the chelating agent is a zinc chelating agent.
[0069] In some embodiments, the present invention provides a black pigment dispersion. The black pigment dispersion includes a mixing vehicle and biochar. In some embodiments, the black pigment may further include additional water and a surfactant.
[0070] The black pigment dispersion typically contains about 5% to about 20% by weight of the varnish / grind vehicle / mixed vehicle, as described above, based on the total weight of the pigment dispersion. For example, the pigment dispersion may contain about 5% to about 15% by weight of the varnish / grind vehicle / mixed vehicle, or about 5% to about 10% by weight, or about 10% to about 20% by weight, or about 10% to about 15% by weight, or about 15% to about 20% by weight, based on the total weight of the pigment dispersion.
[0071] The black pigment dispersion typically contains about 10% to about 40% by weight of biochar based on the total weight of the pigment dispersion. For example, the pigment dispersion may contain about 10% to about 35% by weight of biochar, or about 10% to about 30% by weight, or about 10% to about 25% by weight, or about 10% to about 20% by weight, or about 10% to about 15% by weight, or about 15% to about 40% by weight, or about 15% to about 35% by weight, or about 15% to about 30% by weight, or about 15% to about 25% by weight, or about 10 ... It may contain 5% by weight to about 20% by weight, or about 20% by weight to about 40% by weight, or about 20% by weight to about 35% by weight, or about 20% by weight to about 30% by weight, or about 20% by weight to about 25% by weight, or about 25% by weight to about 40% by weight, or about 25% by weight to about 35% by weight, or about 25% by weight to about 30% by weight, or about 30% by weight to about 40% by weight, or about 30% by weight to about 35% by weight, or about 35% by weight to about 40% by weight.
[0072] When present, the black pigment dispersion typically comprises from about 1% to about 5% by weight of the surfactant, based on the total weight of the pigment dispersion. For example, the black pigment dispersion may comprise from about 1% to about 2% by weight of the surfactant, based on the total weight of the pigment dispersion.
[0073] Surfactants are used to create wetting and / or even distribution of different polarity chemicals. For the combination of biochar pigments in the finished water-based ink, surfactants can have up to 5 times the utility if properly selected for their hydrophilic lipophilic (HLP) balanced structure. Surfactant utility includes: 1) during milling to minimum size of pigment, surfactants prevent (highly polar) biochar from re-agglomerating and / or causing larger particle separation, 2) allow intimate (shearing) contact with (relatively low polarity) rosin-citric acid ester resin during manufacturing of color concentrates (dispersions), 3) maximize resin solids of the finished ink at the target viscosity, 4) allow uniform thickness of wet ink to transfer to the intended substrate, and 5) maintain lateral color uniformity of color during application to substrate. Surfactants always have high and low polarity as part of their structure. The best use (or no use) of surfactants is a very complex decision for the skilled artisan in constructing a finished water-based ink.
[0074] When additional water is added to the pigment dispersion, it is typically added in an amount of about 10% to about 50% by weight based on the total weight of the dispersion. For example, water may be added in an amount of about 10% to about 40% by weight, or about 10% to about 30% by weight, or about 10% to about 20% by weight, or about 20% to about 50% by weight, or about 20% to about 40% by weight, or about 20% to about 30% by weight, or about 30% to about 50% by weight, or about 30% to about 40% by weight, or about 40% to about 50% by weight based on the total weight of the dispersion.
[0075] The composition of the present invention can be applied to any suitable substrate.Preferred substrates include substrates used in flexible packaging.Subsequently, the substrates can be used to prepare articles such as fast food packaging, cups, etc. EXAMPLES
[0076] The present invention is further described by the following non-limiting examples, which further illustrate the invention and are not intended, nor should they be construed, to limit the scope of the invention.
[0077] Examples 1 and 2. Mixed Vehicles A mixed vehicle of the present invention was prepared according to the formulation in Table 1.
[0078] [Table 3]
[0079] The final Example 1 mixed vehicle has a viscosity of 670 cps measured using a Brookfield DV-E Viscometer equipped with a 62 spindle at 30 rpm and a pH=9 at 25°C.
[0080] The primary performance resin in Example 1 is a 100% BRC rosin-citrate resin with an acid number of 210 mg KOH / g. The formula in Example 1 is the wet reaction that occurs between lactic acid and the rosin-citrate resin at a pH of 6.50. The reaction occurs before the esters are fully neutralized. It is believed that the lactic acid creates additional ester bonds in the rosin-citrate resin, lowering the acid number, increasing the molecular weight, and lowering the glass transition temperature (Tg) which creates a film-forming resin at room temperature (25°C) from a non-film-forming rosin-citrate resin. Prior to reaction with lactic acid, the rosin-citrate resin has a Tg above 35°C and is tested as described below, which is responsible for the flexibility. After reaction with lactic acid, the final structure was determined by Sun Chemical Eurolab to be a Diels-Alder addition reaction of lactic acid (alpha hydroxyl structure) to the anhydride moieties of the rosin citric acid resin with a Tg below 25°C, providing the mechanical advantage of greater flexibility.
[0081] The mixed vehicle of Example 2 is similar to the mixed vehicle of Example 1, except that the lactic acid is replaced with additional rosin-citrate ester resin. The formulation of Example 2 is shown in Table 2.
[0082] [Table 4]
[0083] The final Example 2 mixed vehicle has a viscosity of 85 cps as measured using a Brookfield DV-E viscometer equipped with a 62 spindle and a pH=9.6 at 25°C.
[0084] The mixed vehicle of Example 1 exhibits the necessary mechanical strength, whereas the mixed vehicle of Example 2 does not. In general, mechanical strength is a product of surface hardness and flexibility. Surface hardness can be measured using a pencil hardness test, as described below. Flexibility is evaluated by Tg, and those skilled in the art will understand that values below 25°C and above 15°C contribute to mechanical advantages. Compositions with Tg above 30°C may suffer from brittleness. Tg below 15°C may suffer from lack of resistance to mechanical forces in the form of smearing. The Tg property works in conjunction with pencil hardness. Mechanical strength is most often manifested in printing inks as resistance to color transfer or scratching. It is a disadvantage that when an object comes into contact with the print, the dry ink will likely turn into powder and be transferred to skin, clothing, etc. It is an advantage that the dry ink will hold together and flex with the application of mechanical energy without the production of crushed ink or ink powder. Example 2 is mechanically inferior to Example 1 due to its higher Tg (less flexibility).
[0085] [Table 5]
[0086] The chemical modification of Example 1 to lower the Tg ultimately results in the ability to flex (not shatter) and mechanical toughness in the finished ink.
[0087] Examples 3 to 5. Biochar Pigment Dispersion Examples 3-5 are biochar color dispersions. Chemical functionality and subsequent finished ink performance are described below. All three biochar black dispersions utilize the blend vehicle of Example 1 as part of the chemistry. Example 3 uses an anionic surfactant in combination with the 100% BRC blend vehicle of Example 1. Example 4 uses a non-ionic surfactant in combination with the Example. Example 5 omits the surfactant entirely. The formulations of Examples 3-5 are shown in Tables 3-5, respectively.
[0088] [Table 6]
[0089] The black dispersion of Example 3 has a viscosity of greater than 45 seconds in a #2 EZ Zahn cup and a pH=9.0 at 25°C.
[0090] [Table 7]
[0091] The black dispersion of Example 4 has a viscosity of 42 seconds in a #2 EZ Zahn cup and a pH=9.5 at 25°C.
[0092] [Table 8]
[0093] The dispersion of Example 5 flows for a period of time after blade energy is introduced (60 seconds) and then becomes a non-pourable solid. This is known as "setting up". The solid must be agitated to pour. However, the finished ink described that uses this color dispersion does not set up (i.e., remains pourable). Example 5 has a pH=9.3.
[0094] Examples 6 to 8. Finishing inks using the black dispersions of Examples 3 to 5 . Examples 6-8 are finished inks containing the black dispersions of Examples 3 to 5. The formulations of Examples 6-8 are shown in Tables 6-8, respectively.
[0095] [Table 9]
[0096] The finished ink of Example 6 has a viscosity of 31 seconds in a #2 EZ Zahn cup and a pH=9.4 at 25°C.
[0097] [Table 10]
[0098] The finished ink of Example 7 has a viscosity of 35 seconds in a #2 EZ Zahn cup and a pH=9.1 at 25°C.
[0099] [Table 11]
[0100] The finished ink of Example 8 has a viscosity of 40 seconds in a #2 EZ Zahn cup and a pH=8.8 at 25°C.
[0101] Examples 9 and 10. Biochar black pigment dispersions based on prior art chemistry Examples 9-10 are additional biochar black pigment dispersions based on Aquagreen chemistry. The formulations for Examples 9 and 10 are shown in Tables 9 and 10, respectively. Aquagreen is a commercial ink series from Sun Chemical that has been commercially printed / proven functionally robust for over 3 years for the performance properties listed in Tables B, C, and D. These are comparisons in that they have high BRC content but fall short of 100% BRC content. Inks prepared from the black dispersions of the present invention exhibit properties equal to or better than high BRC inks prepared from black dispersions based on commercial chemistry. Pigment dispersions and inks based on Aquagreen chemistry are the closest prior art. It is noted that the Aquagreen composition contains high molecular weight resin emulsions to achieve the required performance properties. Of note, the inks of the present invention achieve the required performance without high molecular weight resin emulsions.
[0102] [Table 12]
[0103] The pigment dispersion of Example 9 has a total non-volatile content (TNV%) of 47.1% and a BRC of 96.7%.
[0104] [Table 13]
[0105] Example 11. Comparative Technical (Mixed) Vehicles . Example 11 is a commercially available technology (mixed vehicle). This is GP37000030A Aquagreen Tech Vehicle, available from Sun Chemical.
[0106] Examples 12 and 13. Comparative Black Finish Ink Examples 12 and 13 are comparative black finished inks prepared using the black pigment dispersions of Examples 9 and 10 and the mixed vehicle of Example 11. The formulations of Examples 12 and 13 are shown in Tables 11 and 12.
[0107] [Table 14]
[0108] The comparative finished ink of Example 12 has a TNV of 45.2% and a BRC of 82.0%.
[0109] [Table 15]
[0110] The comparative finished ink of Example 13 has a TNV of 39.4% and a BRC of 81.5%.
[0111] Example 14. Finished ink performance The following are capabilities of the finished ink utility in flexographic and rotogravure substrate applications.
[0112] Ambient Wet Stability / Initial vs. 1-week Viscosity at Room Temperature A typical water-based printer will print best in the viscosity range of 18 seconds to 35 seconds on a #2 EZ Zhan cup viscometer. Non-reduced inks should be formulated to an uncut viscosity within that range. The ink sample is vigorously shaken by hand for 10 seconds to ensure uniformity. The test records the initial viscosity using a #2 EZ Zhan cup viscometer and the viscosity after 7 days. Viscosity changes (increases or decreases) of more than 5 seconds are unacceptable.
[0113] B. Heated and Wet Stability / 24 hours at 120°F (approximately 49°C) This test is identical to the Ambient Wet Stability Test, except the wet sample is placed in a 120° F. oven for 24 hours before the second viscosity measurement. Viscosity changes (increases or decreases) in more than 5 seconds are not acceptable.
[0114] C. Color strength / application density at 25 sec printing viscosity The ink is reduced to 25 seconds on a #2 EZ Zahn cup using tap water and then applied to C1S bleached paperboard using a 200 line 7.0 BCM hand proofer. The applied ink is dried in a 120°F convection oven for 60 seconds. An X-Rite 939 (Daylight 65, set at 10 step observer) is used to determine the average density (V) of the three readings. This is compared to the standard process density of V=1.40 to determine the optimum anilox selection or range. For rotogravure and flexographic applications, the (cylinder or anilox) volume selection is typically 1.2 BCM (billion cubic microns) to 15.0 BCM. Obtaining color density applied at low BCM (called shallow) is much more difficult than using the higher BCM (deep) options. 7.0 flexo anilox BCM is a typical volume for line artwork, and 2.0 BCM is typical for artwork.
[0115] D. Static heat resistance / Sentinel heat seal machine The Sentinel heat seal machine is set at 40 psi, 400°F, 1 second duration, with the top heated jaw. Ink is applied as in Test C above. The printed sample is aligned against the dull side of the aluminum foil and the construction is inserted into the jaws of the heat seal machine and the clamping shoe is pressed. The construction is allowed to cool to room temperature and the foil is removed from the printed ink surface. Visual transfer of ink to the foil is not a passing result.
[0116] E. Kinetic Heat Resistance / Sutherland Friction Tester Heating Thread This test is specific to the heat lamination process used on pre-printed corrugated substrates. Ink is applied onto the substrate in 7 inch long by 2 inch wide strips (using the printing method described in Test C above). The substrate is affixed ink side down to the bottom of the apparatus. A heated sled is warmed to 400°F. The heated sled is pulled over the surface of the print specimen, passing from the inked areas to the uninked areas. The test is set for 25 cycles. Upon completion, the substrate is inspected for ink transfer to the unprinted areas. Passing performance is no visible ink removal and no transfer of color to the uninked areas of the substrate.
[0117] F. Print quality / filament inspection Using a gloved hand (latex gloved), wet your index finger with a dime-sized amount of ink. Tap the wet index finger against your thumb in 5-second increments until the ink dries. While pulling, inspect the area between your finger and thumb. If filaments (look like spider webs) appear, it indicates that the cohesive / adhesive balance is biased towards cohesion. Filaments that form between the ink plate and the anilox, or between the gravure cylinder and the stock, will lead to ink deposits or casting off into non-printing areas. A passing result is no visible filaments.
[0118] G. Print Quality / Glass Rewet at pH=9 Using the printing method C above, apply ink to a glass substrate and allow the ink to dry on the glass. This simulates ink drying on the anilox plate if the printing run is stopped mid-run for any reason. Prepare a 100g solution of tap water and monoethanolamine (MEA) to pH=9.0 (0.2% MEA required depending on tap water source). Hold the glass substrate with the dried ink facing up at a 45 degree angle and pipette 5ml of pH 9 solution and slowly drip onto the print area 6 inches away. A passing result is complete removal of the ink from the glass in the drip area. That is, rewetting of the ink on the glass plate indicated by removal of the dried ink predicts rewetting at the anilox plate interface. If the ink cannot be rewetted, this will cause ink to build up in non-image areas and ink will be delivered to areas where it should not be delivered, also known as smeared printing.
[0119] H. Print Quality / Gravure dry for 5 minutes then rewet Using a Geiger lab gravure press, load 100 grams of ink #2 EZ Zahn cup into the pan, ramped down to 20 seconds. With the blade engaged, bring the press to 50% speed. Pull a test print as a check control. Stop the press without releasing the blade. Allow the ink to dry in the cylinder for 15 minutes under ambient conditions. This mimics a potential power outage and its effect on plugging the cells. After 15 minutes, begin ramping up the press. Rewet the Geiger cylinder for 5 minutes. Pull another print. Check for evidence of uneven ink delivery. A passing result is when the printed image remains uniform after rewet and does not show a low amount of ink delivery in the areas of the etch containing dried ink.
[0120] Block resistance / front to back ink transfer Prepare a 10 inch long by 3 inch wide strip of printed ink on 20# MG paper (using the printing method described in C above). Roll the print up into a cylinder with your fingers. Fold the cylinder flat into a 1.5 inch by 3 inch configuration. Set the block tester to 120°F, 50 psi, and 66% relative humidity. Place the flattened substrate cylinder into the block tester and leave for 24 hours. Once removed from the block tester, open the sample and inspect for ink transfer from the printed side to the unprinted back side of the stock. A passing result is no visible ink transfer to the back side of the stock.
[0121] J. Mechanical Abrasion / Sutherland Friction A finished ink with a viscosity of 29 seconds is applied to a #2 EZ Zahn cup on the polyethylene (PE) side of a polyethylene coated paper using a 500 line 4.0 BCM hand proofer, dried in a 120°F convection oven for 30 seconds, then cured at ambient conditions for >16 hours. The test is performed using a Sutherland rub tester with a 2# sled and set for 25 cycles. The printed sheet is mounted on a 2# sled (ink side down so that the ink surface is exposed) facing the unprinted PE surface of the same stock, which is mounted on the Sutherland bottom. The test consists of 25 cycles of rubs. The nk density is measured with an X-Rite 939 spectrophotometer using settings D65 light / 10 step observer. Measurements taken from the non-tested areas (i.e., non-ink transferred) of the substrate density are subtracted from the measured density of the highest ink transferred area (major contributions V, C, M, Y) to determine ink transfer only. X-Rite transition density must be less than 0.100 to meet established / historic printing industry mechanical friction requirements. The primary color contribution is determined automatically by many densitometers such as the X-Rite 939. It is the dominant reflectance wavelength of visible light for yellow (Y), magenta (M), cyan (C), and black (V). Examples of dominant absorbance are magenta for pink and cyan for dark forest green. Identifying the dominant absorbance wavelengths ensures that the data includes colors with the highest risk of observed transitions.
[0122] K.BRC / ASTM Method D6866 Samples of the biochar pigment and the mixed vehicle of Example 1 were submitted to Beta Analytical, Miami, FL. Both samples achieved a 100 BRC rating. The BRC content of other materials used in the compositions of the present invention is available in publicly available sampling databases. The contribution of each material in the composition can be calculated by multiplying the % BRC of the material by its weight % in the composition. It should be noted that some items, such as starch, are commonly recognized as 100% BRC.
[0123] L. Microwave Safety The finished ink is applied to 20# MG sandwich packaging stock using the printing method described in C above. The 4" x 2" printed sample is placed in a 1200 watt microwave and a paper cup containing 100g of water is also placed in the microwave (to protect the microwave emitter from burning out). The timer is set for 3 minutes on the high setting. The test will stop if there are any signs of smoke / sparks / flames. If the 3 minutes is completed successfully, the printed sample is removed and inspected for discoloration or heat. A passing result is no evidence of heat, discoloration, sparks, smoke, or flames.
[0124] M. Exercise Water Resistance / Wet Napkin Test This is a Water Wet Napkin - Quantitative Mechanical Rub Transfer Test. Ink is applied to 20# MG sandwich packaging stock and cured (same method as above). The fully water wet napkin is pulled crosswise across 4 inches of print stock with a 2# Sutherland sled on it. A 3" x 4" piece of copy paper is placed between the sled and the wet napkin to hold all layers together during the test. The napkin is then allowed to dry. X-rite 939 density (major contributions V, C, M, Y) is measured for the background with no ink, and for the maximum ink transferred area. The background density is subtracted from the ink transferred area to determine the ink only transfer density. To be accepted by industry standards, historical ink transfer density values must be less than 0.050.
[0125] N. Specific product tolerance - seasonings This test involves gently wiping the condiments over the printed ink and evaluating the transfer of the ink to the napkin. The PE side of PE coated bleached stock is printed with the ink. The test employed the printed / cured PE side of the PE coated stocks listed above. Each condiment (ketchup, mustard, mayonnaise, vegetable oil) is placed over the inked area of the printed stock in a 1 inch (2.54 cm) diameter circle. After 15 seconds, the condiment is removed using a napkin. The napkin is inspected for ink transfer and rated on a scale of 1-5: 1=no visible ink transfer, 2=nearly imperceptible ink transfer, 3=slight ink transfer, 4=moderate ink transfer, 5=excessive ink transfer. A passing result indicates slight to no ink transfer to the napkin (rating of 1-3).
[0126] O. Use of Overprint Varnish (OPV) – Requirements In some embodiments, the mixed vehicle of the present invention can be used as a 100% BRC coating for applications that require an overprint varnish or additional resistance properties. For applications that are not robust to water or mechanical resistance, the mixed vehicle of the present invention is applied to the printed area at a dry application weight of greater than 0.5# / ream using a 200 line 7.0 BCM hand proofer. The coated printed area is then retested for the required properties. Many ink end uses have very extreme resistance requirements, such that an overprint varnish is usually required. One example of such an application that typically utilizes an overprint varnish is pre-printed clamshells or French fries scoops in the fast food packaging market. These packages have OPV over the printed color. Ink transfer is not acceptable where food contact occurs. French fries scoops are shipped in a nested configuration (long tubes inside the next tube) and ink transfer is not allowed.
[0127] Other applications, such as cold cups, often have the option of using OPV depending on end use and processing factors.
[0128] P.Pencil hardness method Wet prospective (i.e., to be tested) composition (which may be a single polymer, vehicle, or finish ink, as appropriate) is applied to the glass using a 1.0 mil Byrd application over a distance of 8 inches. The polymer surface is dried in an air dryer for 30 seconds or until completely dry to the touch. A control polymer of known pencil hardness may be applied to a different area of the glass (each strip should be labeled). The glass is placed on top of a white paper or surface during testing so that no carbon transfer (from the pencil) is overlooked. Hold a 4B pencil comfortably and draw back and forth over a 1 inch area of the top of the test surface. Apply very light pressure to the first patch at a 30 degree angle and heavy pressure to the second patch (over the same area) at an 80 degree angle, but not so heavy that the pencil or graphite tip breaks.
[0129] Evaluate if the carbon transfer is transferred to the print surface and if the surface is altered or destroyed. Evaluate if the polymer feels different when crushed by the pencil. Moving from soft to hard pencils, the first pencil that does not transfer carbon or alter the surface of the print is the surface hardness of the resin (4B, 3B, 2B, FB, F, HB, H, 2H, 3H, 4H). If the pencil used is harder than the test surface, the surface may shatter or powder, or the carbon will not transfer. If the surface shatters or powders, this will be evident on close inspection and can be "felt" by the pencil as disruptive vibrations. Keep in mind that flexibility is different from surface hardness. A shattered surface may allow for carbon transfer. A historical pass result for this test is a hardness of 2H or greater.
[0130] Q. Film formation method This test is used to determine if a polymer will form a film at a desired temperature, such as room temperature (approximately 25° C.). The polymer is applied to a glass surface and allowed to dry. The glass surface is heated to the desired temperature. A series of tests can be performed at different temperatures, such as 25° C., 35° C., etc. A razor blade is used to remove the dried polymer from the glass surface. If the polymer comes off in a sheet, the polymer has formed a film at the temperature to which the glass was heated. If the polymer is a powder, the polymer has not formed a film at that temperature. A passing result is the formation of a film at room temperature that has the mechanical advantage described above.
[0131] result The finished inks of the present invention were tested in several of the performance tests listed above, and the results are shown in Tables B, C, and D below.
[0132] [Table 16]
[0133] [Table 17]
[0134] Where "overprint" is indicated in Table D, this means that the finished ink was also tested after being overprinted with the mixed vehicle of Example 1 used as an overprint varnish.
[0135] [Table 18]
[0136] The performance data shows that all three 100% BRC biochar black inks perform well for the intrinsic and dynamic properties listed. Although not optimal in themselves in some of the intrinsic dynamic properties, Examples 6 and 8 may be recommended for applications that use an overlacquer (i.e., overprint varnish). Current examples of fast food packaging applications with overlacquers include folding cartons, preprinted corrugated board for clamshells, display materials (e.g., Happy Meals), and cold cups. Example 7 is the best 100% BRC recommendation for applications where overprint varnish is not available. Non-overprinted fast food applications include takeaway bags, sandwich packaging, pinch bottom bags, and directly printed clamshells.
[0137] Although the present invention has been described in detail, including preferred embodiments thereof, it will be appreciated that those skilled in the art, upon consideration of this disclosure, may make modifications and / or improvements thereto which are within the scope and spirit of the present invention.
Claims
1. 1. A water-based liquid black ink composition comprising water, a biochar pigment, and a rosin adduct, the rosin adduct having a bio-renewable carbon (BRC) content of 100% based on the carbon content of the rosin adduct; the rosin adduct is a 100% bio-renewable carbon (BRC) rosin adduct which is a rosin ester which is a reaction product of a rosin monomer acid and / or dimer acid with an alpha hydroxy carboxylic acid, and 70% to 100% of the carbon content in the water-based liquid black ink composition is bio-renewable carbon (BRC); A water-based liquid black ink composition.
2. The water-based liquid black ink composition of claim 1, wherein the water, biochar pigment, and rosin adduct are provided as a mixture of: (a) 50% to 70% by weight, based on the total weight of the water-based liquid black ink composition, of a black pigment dispersion, wherein the black pigment dispersion comprises the following components (i) and (ii): (i) 10% to 40% by weight of biochar, based on the total weight of the black pigment dispersion; and (ii) 5% to 20% by weight of a mixed vehicle based on the total weight of the black pigment dispersion wherein the mixed vehicle comprises the following components (1) and (2): (1) 10% to 30% by weight of water, based on the total weight of the mixed vehicle; and (2) 10% to 30% by weight of said rosin adduct, based on the total weight of the mixed vehicle; (b) 30% to 50% by weight of an additional said mixing vehicle, based on the total weight of the water-based liquid black ink composition.
3. The black pigment dispersion is (a) 1% to 5% by weight of a surfactant, or (b) 10% to 50% by weight additional water, or (c) 1% to 5% by weight of a surfactant and 10% to 50% by weight of additional water, all amounts being based on the total weight of the black pigment dispersion. The water-based liquid black ink composition of claim 2 further comprising:
4. The mixed vehicle is (a) 5% to 15% by weight of an L-lactic acid mixture, and / or (b) 10% to 30% by weight of ammonia, and / or (c) 1% to 10% by weight of a wax suspension, and / or (d) 1% to 5% by weight of micronized wax, and / or (e) 0.05% to 1% by weight of a silicone compound, and / or (f) 0.5% to 3% by weight of one or more chelating agents Further comprising: The water-based liquid black ink composition of claim 2 , wherein all amounts are based on the total weight of the mixing vehicle.
5. 5. The water-based liquid black ink composition of claim 4, wherein the wax suspension comprises 25% by weight wax and 75% by weight water, based on the total weight of the wax suspension.
6. 6. The water-based liquid black ink composition of claim 5, wherein the wax is selected from the group consisting of amide waxes, micronized waxes, erucamide waxes, polypropylene waxes, paraffin waxes, polyethylene waxes, polytetrafluoroethylene waxes, carnauba waxes, soy waxes, and combinations thereof.
7. 7. The water-based liquid black ink composition of claim 6, wherein the micronized wax is an ethylene bis stearamide micronized wax.
8. 2. The water-based liquid black ink composition of claim 1, wherein the alpha hydroxy acid is selected from the group consisting of malic acid, lactic acid, tartaric acid, ascorbic acid, citric acid, glycolic acid, 2-hydroxycaproic acid, 2-hydroxycaprylic acid, mandelic acid, phytic acid, and combinations thereof.
9. 10. The water-based liquid black ink composition of claim 1, wherein the rosin ester is further reacted with one or more polyols to provide a high molecular weight modified rosin ester.
10. 10. The water-based liquid black ink composition of claim 1, wherein the rosin is polymerized with an unsaturated compound using a free radical extension process.
11. 2. The water-based liquid black ink composition of claim 1, wherein the rosin adduct is 100% BRC rosin-citric acid ester resin.
12. 12. The water-based liquid black ink composition of claim 11, wherein the rosin-citrate ester resin is modified by further reacting the rosin-citrate ester resin with lactic acid.
13. The water-based liquid black ink composition of claim 1, wherein 80% or more of the carbon content of the water-based liquid black ink composition is BRC (bio-renewable carbon), based on the total carbon content of the composition.
14. The water-based liquid black ink composition of claim 1, wherein 90% or more of the carbon content of the water-based liquid black ink composition is BRC (bio-renewable carbon), based on the total carbon content of the water-based liquid black ink composition.
15. The water-based liquid black ink composition of claim 1, wherein 100% of the carbon content of the composition is BRC (bio-renewable carbon), based on the total carbon content of the water-based liquid black ink composition.
16. (a) 30% to 50% by weight of a mixture vehicle, based on the total weight of the water-based liquid black ink composition; i. 10% to 30% by weight of water, based on the total weight of the mixed vehicle; ii. 10% to 30% by weight of a rosin adduct, based on the total weight of the mixed vehicle; iii. 5% to 15% by weight of an L-lactic acid mixture based on the total weight of the mixing vehicle, the L-lactic acid mixture comprising 88% by weight of L-lactic acid and 22% by weight of water based on the total weight of the L-lactic acid mixture; iv. 10% to 30% by weight of 14.5 Baume ammonia, based on the total weight of the mixed vehicle; v. 1% to 10% by weight of a wax suspension, based on the total weight of the mixing vehicle, the wax suspension comprising 25% by weight wax and 75% by weight water, based on the total weight of the wax suspension; vi. 1% to 5% by weight of a micronized wax, based on the total weight of the mixing vehicle; vii. 0.05% to 1% by weight of a silicone compound, based on the total weight of the mixed vehicle; viii. a mixing vehicle comprising: 0.5% to 3% by weight of a zinc chelating agent, based on the total weight of the mixing vehicle; and (b) 50% to 70% by weight of a black pigment dispersion, based on the total weight of the water-based liquid black ink composition; i. 10% to 40% by weight of biochar, based on the total weight of the black pigment dispersion; ii. 1% to 5% by weight of a surfactant, based on the total weight of the black pigment dispersion; iii. 5% to 20% by weight of the mixed vehicle of part (a), based on the total weight of the black pigment dispersion; iv. 10% to 50% by weight of additional water, based on the total weight of the black pigment dispersion; 2. The water-based liquid black ink composition of claim 1, wherein 75% to 100% of the carbon content in the water-based liquid black ink composition is bio-renewable carbon (BRC).
17. A substrate comprising the water-based liquid black ink composition of claim 1.
18. An article comprising the substrate of claim 17.
Citation Information
Patent Citations
Low VOC content, water-washable lithographic printing ink
JP2007517123A
Water-based ink with high renewable content
JP2020531606A
Sustainable BIO-CHAR-based ink having conductive properties
WO2020220047A1
Plant CHAR carbon pigments and liquid dispersions thereof
WO2021062312A1
High BIO-renewable content printing inks
WO2021138184A1